2010
DOI: 10.2527/jas.2009-2764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal fish oil and seaweed extract supplementation on colostrum and milk composition, humoral immune response, and performance of suckled piglets1

Abstract: An experiment with a 2 x 2 factorial arrangement of treatments (n = 10 sows/treatment) was conducted to investigate the effect of maternal dietary supplementation with seaweed extract (SWE: 0 vs. 10.0 g/d) and fish oil (FO) inclusion (0 vs. 100 g/d) from d 109 of gestation until weaning (d 26) on sow colostrum and milk composition, humoral immune response on d 5 and 12 of lactation, and suckling piglet performance. Furthermore, the influence of dietary treatment on the phagocytic activity of whole blood white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
57
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 41 publications
16
57
2
1
Order By: Relevance
“…Increases in EPA and DHA concentration in sow serum during lactation are consistent with results from Fritsche et al (1993). Because EPA and DHA concentrations were also increased in colostrum and milk from mLCPUFA sows, again consistent with previous findings (Fritsche et al, 1993;Taugbol et al, 1993;Leonard et al, 2010), piglets can also benefit postnatally from maternal mLCPUFA supplementation when litters consume colostrum and milk containing elevated concentrations of EPA and DHA. Both pre-and postnatal exposure to higher EPA and DHA levels may be important to enhance postnatal growth performance.…”
Section: Discussionsupporting
confidence: 89%
“…Increases in EPA and DHA concentration in sow serum during lactation are consistent with results from Fritsche et al (1993). Because EPA and DHA concentrations were also increased in colostrum and milk from mLCPUFA sows, again consistent with previous findings (Fritsche et al, 1993;Taugbol et al, 1993;Leonard et al, 2010), piglets can also benefit postnatally from maternal mLCPUFA supplementation when litters consume colostrum and milk containing elevated concentrations of EPA and DHA. Both pre-and postnatal exposure to higher EPA and DHA levels may be important to enhance postnatal growth performance.…”
Section: Discussionsupporting
confidence: 89%
“…Most researchers found no effect of n-3 LCPUFA supplementation to sows on litter size at birth (Gunnarsson et al, 2009;Mateo et al, 2009;Leonard et al, 2010), whereas others found an increase in litter size (Webel et al, 2003;Spencer et al, 2004;Smits et al, 2011). Rooke et al (2001c) showed a linear decrease in litter size with increasing amounts of salmon oil to the sows diets, but the authors concluded that this finding was unlikely to have been caused by the salmon oil inclusion, as they started supplementing sows at day 60 of gestation, well after the time period at which litter size in the pig is established.…”
Section: Discussionmentioning
confidence: 99%
“…According to Laws et al (2009), increased maternal intakes of β-carotene and vitamin E could increase concentration of colostrum IgG. Moreover, Leonard et al (2010) have reported that the immune modulating properties of β-glucans could increase concentration of colostrum IgG of the sow. According to these observations, daily forages intake by local sows breed could explain their higher colostrum IgG levels.…”
Section: Discussionmentioning
confidence: 99%